PARTISIPASI MASYARAKAT TERHADAP PEMBANGUNAN INFRASTRUKTUR JALAN PERTANIAN MELALUI DANA DESA DI DESA BUHIAS KECAMATAN WORI KABUPATEN MINAHASA UTARA - Michael ., Papudi; Melsje Yellie Memah; Martha Mareyke Sendow (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine community participation in the planning and implementation stages in the construction of agricultural road infrastructure funded by the Village Fund in Buhias Village, Mantehage Island, Wori Sub-district, North Minahasa Regency. The 3-month study was conducted from August to October 2018. Primary data were obtained through interviews, based on a list of questions, to 20 respondents who were chosen based on pusposive sampling method. Secondary data were obtained from the Buhias Village Office, from local bookstores, as well as from the internet through Google searching to obtain journal articles and theses relating to research topics, especially concerning community participation in road infrastructure development. Data analysis using descriptive analysis presented in tabular form. The results showed that community participation in the construction of agricultural road infrastructure in the village of Buhias was in the medium category at the planning stage and in the high category at the stage of implementing agricultural road construction. *eprm*